Simulation of a Power Substation’s Control System Operation - Marek Hoger; Peter Bracinik; Marek Roch (Communications - Scientific letters of the University of Zilina, 2011)
This paper describes a simulator of power substation automation system developed as part of software suit for complex simulation of power substation operation. This software simulates behavior of a distributed control system built from a group of interconnected and cooperating intelligent electronic devices. The basic structure and communication principles are derived from standard IEC 61850.